Dividend Policy and Its Impact on Stock Price – A Study on Commercial Banks Listed in Dhaka Stock Exchange - Al Masum , Abdullah (Global Disclosure of Economics and Business, 2014)
How do dividend policy decisions affect a firm’s stock price, is a widely researched topic in the field of investments and finance but still it remains a mystery that whether dividend policy affects the stock prices or not. There are those who suggest that dividend policy is irrelevant because they argue a firm’s value should be determine by the basic earning power and business risk of the firm, in which case value depends only on the income (cash) produced, not on how the income is split between dividends and retained earnings and opponents of this statement called dividend is irrelevance, that investors care only about the total returns they receive, not whether they receive those returns in the form of dividends, capital gains or both.The results of researches conducted in various stock markets are different. There are many internal and external factors, which simultaneously affect stock prices and it is almost impossible to segregate the effect of each so the variations remain. This paper empirically estimates excess stock market returns for all the thirty banks listed in Dhaka Stock Exchange for the period of 2007 to 2011. Attempts are made to examine, what kind of relationship exists between dividend policy and stock market returns of private commercial banks in Bangladesh, and to what degree the returns on stocks can be explained by their respective dividend policy for the same period of time. Various theories related to dividend policy are tested in various parts of the world with different results and findings. Various other articles are reviewed, written in Bangladesh and abroad to see the significance of dividend policy on the stock prices and to compare the results of this research with those conducted earlier. Sample size is large i.e. all the listed commercial banks of Dhaka Stock Exchange so the results are reliable and valid. Panel data approach is used to explain the relationship between dividends and stock prices after controlling the variables like Earnings per Share, Return on Equity, Retention Ratio have positive relation with Stock Prices and significantly explain the variations in the market prices of shares, while the Dividend Yield and Profit after Tax has negative, insignificant relation with stock prices. Overall results of this study indicate that Dividend Policy has significant positive effect on Stock Prices. JEL Classification Code: D78; E64; H54; R53; G21